More than Grief and Resilience: The Posttraumatic Growth of Grieving Parents by Suicide in Bataan, Philippines - Jayvie Villazor; Rosalito De Guzman (Camarines Sur Polytechnic Colleges, 2022)
The death by suicide of a family member causes adverse disruption to the surviving family. However, a positive transformation following the loss of a loved one by suicide is possible. The present study seeks to describe and elaborate on the essence of a parent's experience in its attempt to overcome grieving and other adverse effects of a loss. Using a descriptive phenomenology design, the researchers conducted face-to-face and virtual semi-structured interviews with nine participants from the province of Bataan, Philippines. The participants are grieving parents who lost their child by suicide from the years 2018 to 2020. The findings revealed 7R of posttraumatic growth (PTG) or themes, namely: relationship with a higher being, reconstruction of parenting style, refined family relations, regard for others, redefined orientation of life, rediscovery of the self, and processing the loss of a child. Furthermore, each theme generated subthemes that elaborated and described a parent's firsthand grieving experience on PTG more in-depth, which can be a basis in making intervention programs and organizing support groups. It can also assist clinicians in knowing the factors that foster and elevate posttraumatic growth in grieving parents by suicide. This study will add to the knowledge of psychotraumatology, thanatology, and suicidology in the Philippines. Finally, further research into the themes of parenting style reconstruction and reprocessing child loss is highly recommended.